2010
DOI: 10.1093/ecam/nen086
|View full text |Cite
|
Sign up to set email alerts
|

Jungle Honey Enhances Immune Function and Antitumor Activity

Abstract: Jungle honey (JH) is collected from timber and blossom by wild honey bees that live in the tropical forest of Nigeria. JH is used as a traditional medicine for colds, skin inflammation and burn wounds as well as general health care. However, the effects of JH on immune functions are not clearly known. Therefore, we investigated the effects of JH on immune functions and antitumor activity in mice. Female C57BL/6 mice were injected with JH (1 mg/mouse/day, seven times intra-peritoneal). After seven injections, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 38 publications
1
74
0
3
Order By: Relevance
“…Numbers of experimental works revealed that propolis and jungle honey possess potent antitumor activity [7, 1517]. However, the existing studies about Nidus Vespae were only confined to the oral diseases [1820], and few studies were carried out to investigate the potential mechanisms by which Nidus Vespae exerts antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of experimental works revealed that propolis and jungle honey possess potent antitumor activity [7, 1517]. However, the existing studies about Nidus Vespae were only confined to the oral diseases [1820], and few studies were carried out to investigate the potential mechanisms by which Nidus Vespae exerts antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated the range of health benefits of honey, which includes anti-inflammatory, antioxidant and wound healing activities (Kassim et al, 2010;Mohamed et al, 2010;Al-Waili et al, 2011;Hussein et al, 2012). Honey was also known to exert anti-cancer effects in several types of cancer cells including colon cancer Fukuda et al, 2011). Malaysian local honey especially Tualang honey has been found to induce anti-proliferative effects on cervical and breast cancer cell lines (Mohamed et al, 2010) as well as anti-bacterial activity against Acinetobacter baumanni (Fauzi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Jungle honey on immune functions and antitumor activity were investigated in mice. It was found that this honey increased peritoneal cell numbers and ROS production, enhanced chemotaxis for neutrophil and IL-1beta mRNA expression in peritoneal cells and Inhibited LL/2 tumour growth [75].…”
Section: Immune Functionmentioning
confidence: 97%